Mental health awareness, stigma, and help-seeking attitudes among Albanian university students in the Western Balkans: a qualitative study - Hyseni Duraku, Zamira; Davis, Holly; Blakaj, Artë; Ahmedi Seferi, Arjeta; Mullaj, Klea; Greiçevci, Viola (Frontiers in Public Health, 2024)
Introduction: The significance of mental health and its impact on overall well-being is increasingly acknowledged across various sectors, including higher education. However, despite this growing recognition, the stigma associated with mental health issues and related help-seeking, particularly within certain cultural groups and socio-economic contexts, continues to pose a formidable barrier to effective care, especially among university students. Addressing these challenges, this study explores the intricate interplay of factors affecting mental health awareness and stigma, including help-seeking behaviors among Albanian university students in three Western Balkan countries: Kosovo, North Macedonia, and Albania. By dissecting these multi-layered influences, this study aims to develop targeted interventions to enhance mental well-being and dismantle barriers to care in these regions. Methods: This qualitative study involved 60 Albanian university students from Kosovo, North Macedonia, and Albania, using focus groups to gather data. The discussions were structured around the socio-ecological model, facilitating a comprehensive exploration of the individual, interpersonal, organizational, and societal factors influencing mental health awareness, stigma, and help-seeking behaviors. Results: Findings from the study indicate a moderate awareness of mental health issues among students. Familial and cultural stigma among Albanians in the Balkans hinder open discussions and access to professional help. There is a notable lack of support from higher education institutions, with only 20% of students reporting that their mental health needs are met. These needs include affordable and confidential counseling, empathetic faculty interactions, and a supportive campus environment. Additionally, there is a lack of continuous and professional help within the community. Societal attitudes deeply rooted in Albanian cultural norms and traditional beliefs perpetuate stigma, limiting effective health care and help-seeking behavior. Discussion: The results emphasize the need for a culturally sensitive and holistic approach to mental health interventions that integrates strategies across multiple levels of the socio-ecological model. Enhancing mental health literacy, reducing stigma, and advocating for supportive legislation and policies in the Western Balkan region are critical. Moreover, the study highlights the urgent necessity for universities in particular to improve their mental health services, which will significantly enhance both the academic success and personal development of students.